Role of Macroeconomic Variables in Entrepreneurship Development: Evidence from Renewable Energy Sector of Nepal - Yadav, Maheshwar Prasad (Nepal Journal of Multidisciplinary Research, 2021)
This study analyzes the impact of macroeconomic variables on entrepreneurship development in renewable energy sector of Nepal. This study examines the effect of GDP, market size in terms of population and number of households, and sales in terms of number of renewable energy systems installed on entrepreneurship development, i.e., number of renewable energy enterprises (REEs) using data from 1992/93 to 2016/17 by estimating various logarithmic models. The study concludes that the most important factor affecting entrepreneurship development is market size followed by GDP and sales in the context of renewable energy sector in Nepal. This study is considered to be useful for REEs, development actors, academia and policy makers creating employment by increasing production and providing energy in the country. The study can be further extended by incorporating the opinion and views of respondents from customers, regulating authorities and development actors in the sector to get greater insight into the results.